Misperception of Vaccine Acceptance to the COVID-19 Vaccine in Indonesia: A Systematic Review - Idris, Haerawati; Zaleha, Siti (Kesmas, 2022)
Vaccination is one of main steps to overcome the continuous increase in the Coronavirus Disease 2019 (COVID-19) pandemic. However, its implementation is hindered by various responses such as acceptance and refusal. This study aimed to describe the perception of the COVID-19 vaccine in Indonesia. A systematic review design was used, and the literature searches were carried out using Google Scholar, PubMed, Science Direct, and WHO COVID-19 databases following the PRISMA guideline process. The keywords used were coronavirus, COVID-19, vaccination, COVID-19 vaccination, vaccine response, vaccine acceptance, vaccine perception, and Indonesia in English or Indonesian articles published in 2020-2021. This study discovered 13 sample articles including six qualitative and seven cross-sectional studies. The responses showed varying results divided into positive, indicating vaccine acceptance, and negative responses that made hesitations to refusal. People with a good response and perception considered the vaccine an antibody to fight the virus. Meanwhile, others who hesitated or rejected were due to their concerns about side effects, safety, and effectiveness. Furthermore, inaccurate information or hoaxes circulating in the community significantly influence people's perceptions.